C.S. Draper papers - Draper, C. S. (Charles Stark); Draper, Martha Washington Stark; Jacoby, John Francis Lucas; Jacoby, Ralph, 1768-1822.
Correspondence, speeches, writings, and consultant and organizational files documenting Draper's career as a professor of aeronautical engineering at Massachusetts Institute of Technology and technical consultant to the Curtiss-Wright Corporation and other airplane manufacturers and to the Sperry Gyroscope Company, inc., American Waltham Watch Company, and other instrumentmakers. Subjects include aircraft navigation, blind flying, and aeronautical instruments, especially gyroscopic inertial guidance, the basis for "automatic pilot" navigational systems. Correspondents include Holt Ashley, Sir Leon Bagrit, Raymond L. Bisplinghoff, Benjamin P. Blasingame, Secor D. Browne, Richard H. Frazier, I.J. Galantin, Howard Wesley Johnson, J. Francis Reintjes, Robert C. Seamans, Jr., and Martin Summerfield.
Papers of Draper's mother, Martha Washington Stark Draper, a founder of the Missouri chapter of the Daughters of the American Revolution, relate chiefly to the history and genealogy of the Draper and Stark families and to Missouri state and local history. Includes a commonplace book and ledger (circa 1773) kept by father and son commission merchants John Francis Lucas Jacoby and Ralph Jacoby. Correspondents include Thomas Benson Whitledge and C.S. Draper's brother, Ralph Clayton Draper.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Engineer, inventor, and educator. Born 1901; died 1987.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ashley, Holt -- Correspondence; Bagrit, Leon, -- Sir -- Correspondence; Bisplinghoff, Raymond L. -- Correspondence; Blasingame, Benjamin P. -- Correspondence; Browne, Secor D. -- 1916-1986 -- Correspondence; Draper, Ralph Clayton -- Correspondence; Frazier, Richard H. -- 1900- -- Correspondence; Galantin, I. J., -- 1910- -- Correspondence; Johnson, Howard Wesley, -- 1922-2009 -- Correspondence; Reintjes, J. Francis -- Correspondence; Seamans, Robert C. -- Correspondence; Summerfield, Martin -- Correspondence; Whitledge, Thomas Benson, -- 1810-1844.; Draper family; Stark family; American Waltham Watch Company; Curtiss-Wright Corporation; Daughters of the American Revolution. -- Missouri Society; Massachusetts Institute of Technology -- Faculty; Sperry Gyroscope Company, inc; Aeronautical instruments; Aeronautics; Aircraft industry; Airplanes -- Piloting; Automatic pilot (Airplanes); Commission merchants -- United States; Engineering; Genealogy; Gyroscopic instruments; Instrument flying; Instrument industry; Missouri -- History; Missouri -- History, Local; Educators; Engineers; Inventors